Control of Nitrogen Exports From River Basins to the Coastal Ocean: Evaluation of Basin Management Strategies for Reducing Coastal Hypoxia. Issue 10 (4th October 2018) - Lee, M.; Jung, C.; Shevliakova, E.; Malyshev, S.; Han, H.; Kim, S.; Kim, K.; Jaffé, P. R.
Abstract: The spread of coastal hypoxia is a pressing global problem, largely caused by substantial nitrogen (N) exports from river basins to the coastal ocean. Most previous process‐based modeling studies for investigating basin management strategies to reduce river N exports focused on the impacts of different farming practices or land use, used watershed models that simplified many mechanisms that critically affect the state of N storage in land, were limited mainly to fairly small basins, and did not span multiple climate regimes. Here we use a process‐based land‐river model to simulate historical (1999–2010) river flows and nitrate‐N exports throughout the entire drainage network of South Korea (100, 210 km 2 ), which encompasses varying climate, land use, and hydrogeological characteristics. Based on projections by using multiple scenarios of N input reductions and climates, we explore the impacts of various ecosystem factors (i.e., N storage in basins, climate and its variability, anthropogenic N inputs, and basin location) on river nitrate‐N exports. Our findings have fundamental implications for reducing coastal hypoxia: (1) a small reduction of N inputs in basins, including intensively utilized human land use, can have a greater improvement on water quality; (2) heightening climate variability may not increase long‐term mean river N exports yet can significantly mask N input reduction effects by producing N export extremes associated with recurring coastal hypoxia; and (3) N exports to the coastal ocean can be most efficiently reduced by decreasing N inputs in subbasins, which are receiving high anthropogenic N inputs and are close to the coast. Key Points: A small reduction of nitrogen inputs in basins, with intensive human land use, can have a greater improvement on water quality Climate variability may not increase long‐term mean river nitrogen exports yet can produce export extremes related to coastal hypoxia Coastal nitrogen exports can be efficiently reduced by targeting basins that are receiving high nitrogen inputs and are close to the coast